Students’ Perceptions on Using Song to Improving Students’ Vocabulary - Elthia, Memy Wardani; Patty, Elyakim Nova Supriyedi (CT. Rajawali media Utama, 2023)
This study investigates the students’ perceptions on using song to improving the student’s vocabulary. Though, the utilization of the songs as a media may have advantages and disadvantages. Thus, a consideration of its strengths and weaknesses is required. To fill the need, this study aimed to identify the strengths and weaknesses of the media as an tools in improving students ‘vocabulary. The narrative inquiry was chosen as the research design to uncover the story or perception of the students towards the use of songs, by conducting interview. The results of the study indicate that: 1) The strength, including ease of access, effective, easily increases the students’ vocabulary.2) the weakness, including most song using the figurative language.